Old dogs and new tricks in antimicrobial discovery. (October 2016) - Butler, Mark S; Blaskovich, Mark AT; Owen, Jeremy G; Cooper, Matthew A
Graphical abstract: Highlights: The threat of growing antimicrobial resistance urgently requires new 'silver bullets'. Traditional approaches to antibiotic discovery are failing to produce new antibiotics. Metagenomic approaches can identify novel structures from unculturable bacteria. Semisynthetic modifications of existing natural products deliver improved antibiotics. Academic synthetic chemical space contains many potential novel antibiotics. Abstract : The discovery of new antibiotics is crucial if we are to avoid a future in which simple infections once again lead to death. New antibiotics were traditionally discovered by analyzing extracts from cultured soil-derived microbes. However, in the last few years only a few new antibiotic classes have been identified using this method. Attempts to apply target-based screening approaches to antibiotic discovery have also proven to be unproductive. In this article, we describe how DNA sequencing and bioinformatic techniques are revolutionizing natural product discovery leading to new natural product antibiotics sourced from both cultivated and uncultivated microbes. New chemical structures are also being 'crowd sourced' from chemists around the world, and 'forgotten' antibiotics repositioned for clinical trials after chemical or biochemical modification of the original natural product. Collectively such approaches have the potential to revamp antibiotic lead discovery and re-invigorate the antibiotic pipeline.